Principles and Applications of Magnetic Bearing Systems - Harvey, A. L.; Kadri, A.; Zmood, R. (Elektronika ir Elektrotechnika, 2001)
Magnetic bearings are used where low friction losses are required, typically for high speed rotating machinery or to reduce friction losses in battery powered devices. This paper discusses the principles and applications of electronic bearing systems commonly referred to as active magnetic bearings (AMB) .AMB’s consist of a rotor position sensor, controller and magnetic actuator. Position sensors are commonly inductive in nature. For multi-axis control, a suitable Digital signal processor board may be used. Sensor-less systems are also used where the position is inferred from actuator variables. Commercial companies such as MECOS provide integrated sensor and digital control systems whilst others provide controller systems only. Magnetic actuators are usually custom designed for the particular application. AMB controller considerations are discussed in some detail in this paper.